Antimicrobial Effects of Sulfonyl Derivative of 2(5H)-Furanone against Planktonic and Biofilm Associated Methicillin-Resistant and -Susceptible Staphylococcus aureus - Sharafutdinov, Irshad S.; Trizna, Elena Y.; Baidamshina, Diana R.; Ryzhikova, Maria N.; Sibgatullina, Regina R.; Khabibrakhmanova, Alsu M.; Latypova, Liliya Z.; Kurbangalieva, Almira R.; Rozhina, Elvira V.; Klinger-Strobel, Mareike; Fakhrullin, Rawil F.; Pletz, Mathias W.; et al. (Frontiers in Microbiology, 2017)
The gram-positive opportunistic bacterium Staphylococcus aureus is one of the most common causatives of a variety of diseases including skin and skin structure infection or nosocomial catheter-associated infections. The biofilm formation that is an important virulence factor of this microorganism renders the antibiotic therapy ineffective, because biofilm-embedded bacteria exhibit strongly increased tolerance to antimicrobials. Here we describe a novel 3-chloro-5(S)-[(1R,2S,5R)-2-isopropyl-5-methylcyclohexyloxy]-4-[4-methylphenylsulfonyl]-2(5Н)-furanone (F105), possessing a sulfonyl group and l-menthol moiety. Minimal inhibitory and bactericidal concentration values (MIC and MBC) of F105 were 10 and 40 mg/L, respectively, suggesting F105 biocidial properties. F105 exhibits pronounced activity against biofilm-embedded S. aureus and increases the efficacy of aminoglycosides (amikacin, gentamicin and kanamycin) and benzalkonium chloride with fractional inhibitory concentration index values of 0.33-0.44 and 0.29, respectively, suggesting an alternative external treatment option, e.g. for wound infections. Moreover, low concentrations (0.5 - 1.3 mg/L) of F105 reduced the MICs of these antimicrobials twofold. By using confocal laser scanning microscopy (CLSM) and CFU/mL counting, we show explicitly that F105 also restores the antimicrobial activity of gentamicin and ampicillin against S. aureus biofilms by several orders of magnitude. Biofilm structures were not destroyed but sterilized, with embedded cells being almost completely killed at twofold MBC. While F105 is quite toxic (CC50/MBC ratio 0.2), our data suggest that the F105 chemotype might be a promising starting point for the development of complex topical agents for combined anti-staphylococcal biofilm-therapies restoring the efficacy of some antibiotics against difficult to tread S. aureus biofilm.